Power BI tips and tricks (Includes time-saving ChatGPT prompts). - We, Dan (Packt Publishing, 2023)
Power BI is a powerful data visualization and analytics tool that enables users to create interactive dashboards and reports. To make the most out of your Power BI projects, ChatGPT can provide expert advice and guidance on how to effectively use Power BI, offering insights and recommendations for optimizing your Power BI projects. ChatGPT can assist in creating visually appealing visualizations, optimizing data models, and exploring advanced analytics capabilities. This course begins with a description and introduction of ChatGPT with Power BI Desktop, its advantages and features, and the use cases in detail. You will learn about dealing with changing Excel sheet names, handling file location changes, creating and using template files, and understanding the different file structure issues. We will then explore circular dependency errors and how to fix them using Power BI. We will advance to understand multiple folder data extraction and finally explore and clearly understand the new DAX functions (Offset, Index, and Window). Upon completing the course, you will learn to solve various problems using Excel files and Power BI Data sources and best practices; solve circular dependencies in Power BI, the M Language, and DAX functions; and use Power BI template files to enhance data modeling/analysis. What You Will Learn Learn to deal with file location changes in Power BI Handle Power BI by combining Excel files with different structures Efficiently extract data from multiple folders in Power BI Deep dive and explore the new DAX functionality Learn to handle Excel sheet renaming issues in bulk Understand circular dependency errors and how to fix them Audience This course is aimed at individuals wanting to become better Power BI developers or solve data issues with Excel files in Power BI. Data analysts, those wishing to follow this career path, and business users who work with Power BI and need to create DAX calculations will immensely benefit from this course. The prerequisites include having basic Power BI knowledge and attending the author's Power BI Masterclass for beginners to advanced first as an advantage. This course focuses strongly on Excel data sources and solving data issues and does not cover visualizations in Power BI Desktop. About The Author Dan We: Daniel Weikert is a 33-year-old entrepreneur, data enthusiast, consultant, and trainer. He is a master's degree holder certified in Power BI, Tableau, Alteryx (Core and Advanced), and KNIME (L1-L3). He is currently working in the business intelligence field and helps companies and individuals obtain vital insights from their data to deliver long-term strategic growth and outpace their competitors. He has a passion for learning and teaching. He is committed to supporting other people by offering them educational services and helping them accomplish their goals, gain expertise in their profession, or explore new careers.